FRACTOGRAFIC EXAMINATION OF WELDS WITH STRENGTH MISMATCHING - Praunseis, Zdravko; Avsec, Jurij; Marčič, Simon (Journal of Energy Technology, 2024)
Many investigations of cleavage fracture have shown that the normal stresses in welds with strength mismatching have good correlation with the cleavage fracture behaviour of materials. The objective of this investigation was to find evidence for the microstructural mechanisms leading to cleavage fracture. Examinations of the centre of the macroscopic river patterns at high magnifications revealed fine river patterns. These river patterns could be traced to a single area containing one to a few cleavage facets. These areas are referred to as initiation sites of welds with strength mismatching.